Peran Pajak sebagai Instrumen Penyokong Pendidikan Inklusif untuk Meningkatkan Human Development Index (HDI) Indonesia: Sebuah Studi Literatur - Ilham Febri Budiman (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
Taxes are the largest source of revenue in the structure of Indonesia's state budget (APBN). The revenue will be allocated for state spending, one of which is on education. The education sector is a mandatory spending area amounting to 20% of the total state revenue. This paper aims to identify the role of taxes in supporting inclusive education to improve Indonesia's Human Development Index (HDI). The approach used in this research is qualitative with a literature study method using secondary data sources. The research results show that the increase and decrease in tax revenue affect the size of the education budget due to the dominant contribution of taxes to state revenue. HDI is influenced by indicators such as life expectancy, literacy rate, average years of schooling, and real per capita expenditure, all of which can be improved through inclusive education. Therefore, it can be concluded that if tax revenue increases, the education budget will also increase, and it will be able to fund inclusive education. Inclusive education will drive the increase in Indonesia's HDI. Some of the educational issues that occur include education that is not yet fully inclusive, the low quality of teachers, and the uneven distribution of school facilities and infrastructure. These problems can be resolved if there is significant educational funding, which is also influenced by tax revenue.